2017
DOI: 10.1073/pnas.1618656114
|View full text |Cite
|
Sign up to set email alerts
|

LGI1 tunes intrinsic excitability by regulating the density of axonal Kv1 channels

Abstract: Autosomal dominant epilepsy with auditory features results from mutations in leucine-rich glioma-inactivated 1 (LGI1), a soluble glycoprotein secreted by neurons. Animal models of LGI1 depletion display spontaneous seizures, however, the function of LGI1 and the mechanisms by which deficiency leads to epilepsy are unknown. We investigated the effects of pure recombinant LGI1 and genetic depletion on intrinsic excitability, in the absence of synaptic input, in hippocampal CA3 neurons, a classical focus for epil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
105
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 84 publications
(122 citation statements)
references
References 33 publications
9
105
2
Order By: Relevance
“…While the effects of manipulations in D‐type currents have been studied intensively in many neuron types using the antagonist α‐dendrotoxin, K v 1‐related A‐type currents have been less extensively studied. Previous experiments have found that K v 1.1 and K v 1.4 channels may conduct A‐type currents when co‐assembling with auxiliary subunits K v β1 or K v β2 . Although our simulations suggest that changes in A‐type currents do not significantly affect neuronal excitability, further investigation is required to understand their role in neurons.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…While the effects of manipulations in D‐type currents have been studied intensively in many neuron types using the antagonist α‐dendrotoxin, K v 1‐related A‐type currents have been less extensively studied. Previous experiments have found that K v 1.1 and K v 1.4 channels may conduct A‐type currents when co‐assembling with auxiliary subunits K v β1 or K v β2 . Although our simulations suggest that changes in A‐type currents do not significantly affect neuronal excitability, further investigation is required to understand their role in neurons.…”
Section: Discussionmentioning
confidence: 70%
“…Associated epilepsy phenotypes can be refractory to existing antiepileptic medications, often with devastating sequelae. LGI1 encodes a protein that regulates the expression and function of K v 1 channels and AMPA receptors . In LGI1 knockout models, the expression of K v 1.1 and K v 1.2 channels is reduced by more than 50% .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeted deletion of Lgi1 in mice resulted in lethal myoclonic epileptic seizures . CA3 neurons of Lgi1 −/− hippocampal slice cultures exhibited an increased intrinsic neuronal excitability that may explain seizure generation …”
mentioning
confidence: 99%
“…The highly consistent association between a distinctive clinical phenotype and the presence of LGI1 antibodies strongly suggests that they have a pathogenic role. This has been strengthened by in vitro data that implicate alpha‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid (AMPA)‐receptors and potassium channels in the downstream mechanisms of LGI1‐modulation induced neuronal dysfunction . Other functional effects of the LGI1 autoantibodies include the downregulation of the LGI1 complex, which includes LGI1's natural binding partners a disintegrin and metalloproteinase domain‐containing protein 22 and 23 (ADAM22/23) .…”
Section: The Nsab‐mediated Syndromes and Their Related Immunologymentioning
confidence: 99%